INFORMATION DETECTION OF BID-ASK SPREAD AND FIRM SIZE ON EARNING MANAGEMENT WITH GOOD CORPORATE GOVERNANCE AS A MODERATING VARIABLE - Putri, Roostina Nugrahani (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2024)
The objective of this research is to examine how bid-ask spread and company size impact earnings manipulation, with effective corporate governance acting as a moderating factor. This research employs a quantitative method by analyzing secondary data sourced from the annual reports of manufacturing businesses that are publicly traded on the Indonesia Stock Exchange (IDX) between 2018 and 2022. Samples were collected using purposive sampling with specific criteria. The results showed that a larger bid-ask spread can result in more earnings manipulation, while company size does not significantly affect earnings manipulation. Good corporate governance affects the bid-ask spread and earnings management relationship, but not the company size and earnings management relationship. This study highlights the significance of implementing good corporate governance in reducing earnings management practices and advises investors to consider corporate governance before investing.